Joint Line Restoration in a Contemporary Revision Knee System - Hitt, Kirby; Bhowmik-Stoker, Manoshi; Howard, Michael; Mittal, Yogesh; Heekin, R. David; Jacofsky, David (The Journal of Knee Surgery, 2015)
We investigated a new revision total knee arthroplasty device and associated instrumentation to determine if it could reduce intraoperative complexity and restore the joint line through the arc of motion. In a prospective multicenter study, a total of 95 consecutive patients undergoing a revision knee arthroplasty were evaluated. Medical history, functional health scores, and intraoperative data were collected. The joint line was restored to 28 mm ± 5 mm in full extension and 90-degree flexion. Significant improvements were noted in all functional and general health scores. The anatomic boss position may allow for a reduction in instrumentation, as the need for femoral offset adapters was limited. Joint line restoration with proper posterior condylar offset correlated with positive functional outcomes.
Keywords: joint line restoration; revision knee arthroplasty; functional recovery